1976
DOI: 10.1095/biolreprod14.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Successful Culture in vitro of Bovine Embryos to the Blastocyst Stage

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1978
1978
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…Without defense mechanisms against active oxygen, the superoxide anion redicals, which are the major species of active oxygens and generated within the embryos or in the culture medium under a high oxygen tension, might react with proteins or lipids located in the vicinity and subsequently might cause the inactivation of enzymes (6) or lipid peroxidation of membranes (22). It has been reported that a low oxygen concentration (5%) was beneficial to embryo development in vitro in mice (43), sheep (38), and cows (44). Recently, Noda et al demonstrated a marked increase in the rate of blastocyst formation in the medium containing SOD under a low oxygen tension (5%), when compared with that in the medium without SOD under a low oxygen tension or in the medium containing SOD under a 20% oxygen tension (32).…”
Section: Discussionmentioning
confidence: 99%
“…Without defense mechanisms against active oxygen, the superoxide anion redicals, which are the major species of active oxygens and generated within the embryos or in the culture medium under a high oxygen tension, might react with proteins or lipids located in the vicinity and subsequently might cause the inactivation of enzymes (6) or lipid peroxidation of membranes (22). It has been reported that a low oxygen concentration (5%) was beneficial to embryo development in vitro in mice (43), sheep (38), and cows (44). Recently, Noda et al demonstrated a marked increase in the rate of blastocyst formation in the medium containing SOD under a low oxygen tension (5%), when compared with that in the medium without SOD under a low oxygen tension or in the medium containing SOD under a 20% oxygen tension (32).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that oxidative stress exerts adverse effects on embryonic development following the implantation stage of development. Alternatively, culturing of embryos at the early stage of development under 5% 02 has been shown to be highly effective in a variety of mammalian species (35,42), including mice (4,30,39). It is considered that embryos after the implantation stage may be more resistant to oxidative stress than those in the early embryonic stage.…”
Section: Resultsmentioning
confidence: 99%
“…Without defense mechanisms against active oxygen, the superoxide anion radicals, which are the major species of active oxygens, might react with proteins or lipids located in the vicinity and subsequently might cause the inactivation of enzymes (9), or lipid peroxidation of membranes (27). It has been reported that a low oxygen concentration (5%) was beneficial to embryo development in vitro in many species (44,50,52). Furthermore, SOD activity in the oviduct fluid was significantly higher than that in the serum by ESR assay (33).…”
Section: Distribution Of Cuzn-sod In Genital Organsmentioning
confidence: 92%